PERANCANGAN NETWORK MONITORING SYSTEM (NMS) DAN SYSLOG SERVER MENGGUNAKAN LIBRENMS PADA PT. MAXINDO MITRA SOLUSI - Marwan, Marwan; Putra, Jordy Lasmana (Politeknik Negeri Batam, 2023)
The development of the internet has become an important part of modern life and plays a significant role in shaping the current digital world. PT Maxindo Mitra Solusi, as one of the internet service provider companies which of course needs to have a very good infrastructure, monitoring the network conditions requires an application known as the Network Monitoring System (NMS) and a Syslog Server, both of which are essential for monitoring customer network devices such as routers, switches, access points, and servers. The current issue faced by the network administrators is the lack of detailed information, such as CPU load resources and historical logs, on each target device being monitored. This study aims to propose a design of a network monitoring system and Syslog server at PT Maxindo Mitra Solusi. The benefits of this study lie in enhancing the service provided to customer networks by offering regular monitoring and surveillance. LibreNMS is one of the network monitoring system applications based on a Simple Network Management Protocol (SNMP), which quite a lot provides support features for customer network monitoring. One of these support features is Syslog Server, which provides historical log information for each monitored target device. Based on the results of the conducted research, LibreNMS shows potential in delivering an effective monitoring system and assisting network administrators in early troubleshooting of disruptions that may occur in customer networks.